Lalor, Davitt et Connolly, ou l’avènement de l’aile gauche du mouvement révolutionnaire irlandais, 1846-1916 - Olivier Coquelin (Revue LISA)
Far from being monolithic, contemporary Irish nationalism is divided into several different and even antagonistic tendencies. Thus mainly legalist and reformist-oriented “constitutionalists” are opposed to seditious and subversive-oriented revolutionaries. In the ranks of the latter, moreover, is a trend which originated in the 19th century. Initiated by Lalor, Davitt and Connolly, from 1846 to 1916, the left wing of the Irish revolutionary movement is characterized by objectives combining national revolution and social revolution. The present analysis of its three ideological mentors will thus provide a first indication of its influence on political and social Ireland in the contemporary era.